KAPABILITAS SUPPLY CHAIN TERHADAP JARINGAN KEWIRAUSAHAAN, ORIENTASI KEWIRAUSAHAAN, DAN KINERJA UMKM - Rahmi Widyanti; Husnurropiq Husnurropiq; Deli Anhar; Basuki Basuki; Kurniaty Kurniaty (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
The performance of small and medium enterprises (MSMEs) has a large role in Indonesia's economic growth. The literature and previous research discussing performance is increasing, however, there are contradiction. To identify the reasons behind the contradiction, this research was conducted with the aim of identifying the influence of supply chain capabilities developed by entrepreneurial networks and entrepreneurial orientation. This study collects data from a sample of SMEs registered in the South Kalimantan region which are connected through a closed network and are part of a group. Data was collected through an electronic questionnaire, and 327 MSMEs were contacted to participate in the survey by purposive sampling. Structural equation modeling is applied to identify direct and indirect impacts. The results of the study found that among the selected MSMEs, entrepreneurial networks had an insignificant impact; However, entrepreneurial orientation has shown a significant positive impact. Furthermore, the mediating role of dynamic capabilities is significant in both relationships. The results of the study suggest that SMEs must develop a strong network and must consider strategic alliances to gain competitive advantage.